2015
DOI: 10.1186/s13256-015-0638-0
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection with Corynebacterium aurimucosum after urethroplasty stricture of the urethra: a case report

Abstract: IntroductionCorynebacteria have an important place among the commensal flora of the skin and mucous membranes. Except for Corynebacterium diphtheriae, they were once considered contaminants of mucosa. Recent publications in medical bacteriology have highlighted the importance of several species, such as C. aurimucosum. To the best of our knowledge, we report the first isolation of this strain from urine.Case presentationWe report a case of a patient with a urinary tract infection with C. aurimucosum. We isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…C. aurimucosum causes bacteremia and is associated with spontaneous abortions (2). It can also be isolated from urogenital sites, but only case reports have identified it as a urinary tract pathogen (24). In this study, we identified 3 of 14 clinically significant C. aurimucosum isolates in urine.…”
Section: Discussionmentioning
confidence: 69%
“…C. aurimucosum causes bacteremia and is associated with spontaneous abortions (2). It can also be isolated from urogenital sites, but only case reports have identified it as a urinary tract pathogen (24). In this study, we identified 3 of 14 clinically significant C. aurimucosum isolates in urine.…”
Section: Discussionmentioning
confidence: 69%
“…Both of these factors are critical in determining whether the presence of a microorganism poses a risk to human health. Health-relevant microorganisms detected in PMA-treated ISS samples included a number of Corynebacterium species known to cause opportunistic and urinary tract infections, including C. aurimucosum , C. pseudogenitalium , and C. urealyticum [ 45 47 ]. Opportunistic Aspergillus species were also identified, although at much lower abundance levels.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noticed, however, that metagenomics analysis of leukemia patients showed bacterial reads for P. acnes , Staphylococcus spp., and C orynebacterium spp . and that C. aurimucosum was identified in a patient with a urinary tract infection and C. metallidurans in a patient suffering from nosocomial septicemia …”
Section: Discussionmentioning
confidence: 97%